Linguistic Synergy of Nature and Science in Haibuna Skincare Branding: A Critical Multimodal Discourse Analysis - Malinda Joan Caesarla; Vivi Vellanita Wanda Damayanti (EDUPEDIA Publisher, 2026)
Purpose – This study aims to analyze the structural and conceptual synergy between natural elements and scientific terminology in Haibuna Skincare’s product branding through a critical multimodal discourse analysis approach. Methodology – Utilizing a qualitative descriptive research design, this study examines the product names and visual packaging of Haibuna Skincare. The data were analyzed by integrating Critical Discourse Analysis (CDA) with a multimodal framework that evaluates textual data, visual iconography, and internal laboratory chemical formulation data. Findings –The findings reveal that Haibuna strategically employs morphosyntactic compounding processes to bridge the domains of nature and science within its nomenclature. These lexical choices are consistently validated by packaging iconography and active chemical ingredients, thereby establishing a credible